Do emissions from landfill fires affect pregnancy outcomes? A retrospective study after arson at a solid waste facility in Sicily. Issue 7 (4th July 2019) - Mazzucco, Walter; Tavormina, Elisa; Macaluso, Maurizio; Marotta, Claudia; Cusimano, Rosanna; Alba, Davide; Costantino, Claudio; Grammauta, Rosario; Cernigliaro, Achille; Scondotto, Salvatore; Vitale, Francesco
Abstract : Objectives: In response to public health concern about effects of arson at solid waste management plants in July 2012, we analysed vital statistics data to evaluate any potential effect on pregnancies at different gestational ages of pollutants emitted from the landfill on fire. Setting: A community living near the largest landfill plant in Sicily. Participants: The study group comprised 551 births, live births and stillbirths from pregnancies of mothers residing in the extra-urban exposed area, conceived during a 40 week period during which the highest fire's peak might have influenced pregnancy. Primary and secondary outcome measures: Birth outcomes (gestational age <37 and <32 weeks, low birth weight, very low birth weight and small for gestational age) in the study group were compared with the ones of a reference group of women residing in areas of Sicily with similarly low population density and industrial development. Results: Among singleton live births we observed a three-fold increase in risk of very preterm birth between the extra-urban area and the remaining low inhabitants density and unindustrialised areas for births whose pregnancies were in the third trimester (OR adjusted for maternal age and infant gender=3.41; 95% CI 1.04 to 11.16). There was an excess of very low birth weight singleton infants in the study group as compared with the reference group, which was limited to births to mothers exposed during periconception period (OR adjusted for maternal age and infant gender=4.64; 95% CI 1.04 to 20.6) and first trimester (OR adjusted for maternal age and infant gender=3.66; 95% CI 1.11 to 12.1). The association estimates were imprecise due to the small number of outcomes recorded. Conclusions: The study documented an excess of very preterm and very low birth weight among infants born to mothers exposed to the landfill fire emissions during conception or early pregnancy.